Stress and Coping among Nurses Working at Critical Care units of Selected Hospitals, Nepalgunj Nepal - Acharya, Sunita; Thakuri , Karishma Singh; Acharya, Sarita (Academia Research Journal, 2025)
Stress in the nursing profession has been a persistent global problem for many years now. Study is done to assess the stress and coping among the nurses working at critical units using descriptive cross-sectional study design among 81 critical care nurses of Nepalgunj Medical College Teaching Hospital, Nepalgunj and Nepalgunj Medical College Teaching Hospital, Kohalpur, Nepal. Non probability convenient sampling with all complete population were included Data were analyzed by using descriptive and inferential statistics. Out of 81Majority 56 (69.1%) of the nurses had mild level of stress scores whereas 25(30.9 %) were under moderate stress scores and no body was found under sever level of stress scores. The mean stress score was 43.26 ± 12.19 SD. Majority 53 (65.4%) of the nurses had average coping levels of coping scores whereas 28 (34.6%) had good level of coping scores and nobody had poor level of coping strategies. The mean coping score was 48.48, ± 9.19 SD. There was a positive correlation between level of stress (mean ± SD = 43.26 ±12.19) and the level of coping strategies (mean ± SD = 48.48 ±9.19), with Karl Pearson’s Correlation Coefficient; r=0.18. Study presents mild level of stress and average coping among these nurses.